Identification of Indicators, Components, and Dimensions for the Development of Blended Learning Management in Technical and Vocational Schools of Tehran Province - Ahangari, Mohammad Mehdi; Ahmadi, Amineh; Ahghar, Ghodsi; Taleb, Zahra (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aimed to identify the indicators, components, and dimensions of blended learning management development in technical and vocational schools in Tehran Province. Methods and Materials: This qualitative study employed a thematic analysis approach using semi-structured interviews with 20 experts, including vocational school teachers and academic professionals specializing in educational management. The statistical population consisted of scientific documents, books, research articles, and dissertations from domestic and international databases between 2017 and 2023. The purposive sampling method was applied, and data collection involved semi-structured interviews and a researcher-developed questionnaire. Data were analyzed using MAXQDA software, following open, axial, and selective coding techniques. To ensure trustworthiness, the study applied criteria for credibility, transferability, dependability, and confirmability. Findings: The findings identified five key dimensions, 18 components, and 70 indicators for blended learning management development. The content design and development dimension included defining learning goals, selecting and evaluating educational resources, designing learning activities, and structuring content. The technology and educational tools dimension encompassed selecting appropriate technologies, integrating technology into content, and training in technology use. The assessment and feedback methods dimension included evaluating learner and instructor performance, assessing educational tools, and structured feedback. The management and organization dimension covered data analysis, prioritization, and improvement program implementation. The support and guidance dimension included supplementary training, security and privacy, technical support, and guidance resources. The study emphasized that blended learning management should align with students’ needs, industry demands, and active learning strategies. Conclusion: Blended learning management development requires a systematic approach integrating educational technologies, diverse assessment methods, structured content design, and continuous improvement strategies. The study recommends using multimedia educational materials, active learning methodologies, web-based learning management systems, video conferencing tools, and diverse assessment techniques to enhance learning effectiveness. Limitations included the use of semi-structured interviews and the study’s geographic focus on Tehran Province, excluding other regions.